Physicochemical Characterization of Oleanolic Acid-Human Serum Albumin Complexes for Pharmaceutical and Biosensing Applications - Dopierała, Katarzyna (Langmuir : the ACS journal of surfaces and colloids, 2020)
Among numerous compounds found in marine organisms, triterpenes have attracted considerable research interest due to a beneficial impact on health including anti-inflammatory, antitumor, antiviral, and antioxidation effects. Specifically, new functionalities of oleanolic acid (OLA) have been revealed recently, indicating possible applications in nutrition and pharmaceuticals. However, this bioactive material has limited value due to low water solubility and stability. Therefore, oleanolic acid needs a carrier that protects it and enables controlled release in the human body. Innovative drug delivery systems provide a promising strategy for overcoming these problems. However, the development of those systems requires a comprehensive understanding of the physicochemical properties of triterpenes and their carriers as well as the interactions between them. Among numerous substances, human serum albumin (HSA) has been widely studied as a drug carrier. In addition, human serum albumin is the main blood plasma protein responsible for the transport of drugs and metabolites; therefore, the interactions between that protein and other substances are of physiological and pharmaceutical importance. Moreover, sensing the HSA level in blood plasma is an important challenge that requires binding studies on a molecular scale. The aim of this study was to investigate the properties of oleanolic acid in the presence of human serum albumin in terms of thermodynamics, morphology, and viscoelasticity at the air/water interface. Moreover, the wettability, surface free energy, and topography of the films after deposition on the solid substrate were determined. The results have been discussed in terms of providing physicochemical insight into the interfacial behavior of the OLA-HSA complex, which is crucial for pharmaceutical and bioanalytical applications